MyNote: Multiplatform Reactive Integration System with The Clean Architecture Development Concept - Arrijal Amar Ma'ruf; Dedi Gunawan (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2023)
The application needs in the current digital era are very broad and varied. In its development, these applications undergo a transformation, thus demanding application developers to create applications that suit their devices. This study applies the concept of the reactive paradigm which is implemented into a multiplatform application system and the concept of clean architecture in the process of creating a simple note management application "MyNote". The concept of reactive programming uses Spring WebFlux on the backend and React.js with RxJs on the frontend. The multiplatform concept on Android is implemented in Webview. Performance analysis is conducted using the load test, and stress test. This research aims to provide information on how to implement the concept of multiplatform applications and reactive programming with the clean architecture development method for the MyNote application. In addition, it also can be used as a consideration in implementing this concept stack in production-ready products. This study succeeded in making the MyNote application using a combination of clean architecture, multiplatform, and reactive programming concepts with a percentage of 93,75% application of the concept, and 80% application development.